A MODERN VIEW OF THE PROBLEM OF CARDIOVASCULAR DISEASES IN WOMEN - Qobiljonova Shaxnoza Rustamovna; Abdurashidova Zilola Akbarjon qizi; Xasanova Gulshoda Xasanovna; Sarimsoqova Mohinur Nosirjonovna (Modern American Journals, 2025)
Cardiovascular diseases (CVD) remain the leading cause of death worldwide. Despite this, historically, clinical attention to CVD in women has been insufficient. Only in recent decades have physicians and researchers increasingly recognized that the pathophysiology, manifestations, and risk factors of CVD in women have their own characteristics. This modern view is important not only for diagnosis, but also for prevention and therapy. Despite modern diagnostic and treatment methods, cardiovascular diseases (CVD) remain a leading cause of both morbidity and mortality.